Kelayakan Komposit Rpet -Karbon Aktif Sebagai Filamen 3D Studi Eksperimental Terhadap Sifat Mekanik - Meriatun Meriatun; Sugianto Sugianto; Hasdiansah Hasdiansah (Jurnal Inovasi Teknologi Terapan, 2026)
The accumulation of plastic waste, particularly polyethylene terephalate (PET), has become a serious environmental issue due to its widespread use and long degradation period. Although recycling PET waste offers environmental and economic benefits, its limited mechanical properties restrict its potential application in advanced manufacturing such as 3D printing. Previous studies have shown that reinforcement with carbon-based fillers can improve the performance of recycled PET;however, research on the mechanical characterization of recycled PET composites reinforced with activated carbon remains limited. This study aims to examine the feasibility of polymer composites made from recycled PET reinforced with activated carbon as a raw material for 3D filament production. Recycled PET was mixed with various amounts of activated carbon and mechanically tested according to ASTM D638 (tensile test) and ASTM D256 (impact test). The results showed that the addition of activated carbon affected the tensile strength, elastic modulus, and impact toughness. The optimum composition was obtained at 2.25 g of activated carbon, which provided the best impact resistance. However, the low elongation indicated brittle behavior, suggesting that further modification is required. This study provides an alternative approach for utilizing recycled PET plastic waste as a sustainable and functional material for 3D printing filament